A measurement of the energy loss spectrum of 150 GeV muons in iron - Berger, E; Blair, R; Fuess, T; Guarino, V; Hill, N; Magill, S; May, E; Nodulman, L; Price, L; Proudfoot, J; Stanek, R; Underwood, D; et al. (1997)
The energy loss spectrum of 150 GeV muons has been measured with a prototype of the ATLAS hadron calorimeter in the H8 beam of the CERN SPS. The differential probability dP/dυ per radiation length of a fractional energy loss υ = ΔE μ/E μ has been measured in the range υ = 0.01 ÷ 0.95; it is compared with the theoretical predictions for energy losses due to bremsstrahlung and production of electron-positron pairs or of energetic knock-on electrons. The integrated probability ∫ 0.01 0.95(dP/dυ)dυ is (1.610 ± 0.015 stat ±0 .105 syst)·10 -3 in agreement with the theoretical predictions 1.556·10 -3 and 1.619·10 -3. Agreement with theory is also found in two intervals of υ where production of electron-positron pairs and knock-on electrons dominates. In the region of bremsstrahlung dominance (υ = 0.12 ÷ 0.95) the measured integrated probability (1.160 ± 0.040 stat ± 0.075 syst)·10 -4 is in agreement with the theoretical value of 1.185·10 -4, obtained using the Petrukhin and Shestakov description of the bremsstrahlung process. The same result is about 3.6 standard deviations (defined as the quadratic sum of statistical and systematic errors) lower than the theoretical prediction of 1.472·10 -4, obtained using Tsai's description of bremsstrahlung. © Springer-Verlag 1997.